Aplicación web para el agendamiento de citas médicas en el consultorio médico San Benito de la ciudad de Catamayo - Mite Yaguana, Joel Gabriel (2023)
This thesis project describes the development of a web application for medical appointment scheduling. The developed system facilitates the procedure by recording unique medical records and filing medical appointments patients receive. This way, the need to carry out these processes manually is eliminated. The patient care process has significantly improved thanks to the web application San Benito, which focuses on the integral health area; through the management of patients, medical appointments, medical records, and medical consultations. We developed this web for health professionals and patients who need to make a remote medical appointment. For its coding, both the PHP programming language with the Laravel framework were used. In addition, Bootstrap libraries were the support for the visual aspect. Likewise, The rendering of the views used Blade technology, and the reactivity and functionality in the medical appointment reservation employed Vuejs, together with MySQL and ORM Eloquent for the database management and the mapping of the information. In order to obtain the system requirements, techniques such as surveys and interviews were applied, which allowed the identification of the problem and, in turn, the most optimal solution to it. For compliance and development of each of the phases of the web application, we used the XP methodology, and the IEEE 830 standard and the Kruchten 4+1 architecture. In this way, the realization of the acceptance tests of the system in the San Benito medical office in the city of Catamayo finished. As a result, it was possible to meet the objectives set in the thesis project and answer the research question. We verified that the developed solution positively influenced the San Benito medical office, optimizing registration times to schedule a medical appointment between the patient and the doctor. Keywords: Medical appointment scheduling., Laravel, XP Methodology, Bootstrap, MySQL